Education and pro-family altruistic discrimination against foreigners: Five-country comparisons - Shusaku Sasaki; Naoko Okuyama; Masao Ogaki; Fumio Ohtake (Osaka University, Institute of Social and Economic Research (ISER), 2017)
We measure differences between altruism toward a family member and toward an unknown foreigner using hypothetical questions in internet surveys across five countries: Germany, the US, Singapore, South Korea, and Japan. Our analysis shows that people in all five countries exhibit greater altruistic tendencies toward family members compared to their behavior toward foreigners. However, the degree of discrimination differs across countries. It is lowest in Germany and largest in Japan; the remaining three countries fall within this demarcated range. Further analysis shows that correlation structures between education and altruistic discrimination differ widely. In Germany, people who have spent less time in education exhibit lower altruism toward foreigners compared to toward family members. However, in Japan, South Korea, and Singapore, people with higher education levels tend to discriminate against foreigners. The degree of discrimination is insensitive to the educational background in the US sample.
Keywords: D64; F22; J01; 330; Altruism; Attitude toward foreigners; Immigration; Education; Blinder-Oaxaca Decomposition